A systematic process synthesis method towards sustainable extractive distillation processes with pre-concentration for separating the binary minimum azeotropes - Zhang, Xiaodong; He, Jie; Cui, Chengtian; Sun, Jinsheng (Chemical engineering science, 2020)
•A systematic synthesis method for extractive distillation with pre-concentration.•The energy consumption bottleneck of the extractive distillation column was analyzed.•Replacing the pre-concentration column with a pre-stripper lower remixing effect.•The modified two-column configuration could enhance overall sustainability.•A further intensified dividing-wall column was found not always advantageous. A systematic process synthesis method is investigated towards sustainable extractive distillation with pre-concentration. To approach energy saving, it is one of the common senses to eliminate the infamous remixing effects. In detail, the energy consumption bottleneck is initially analyzed to come at the inspiration to replace the pre-concentration column with a pre-stripper. Afterwards, a two-column scheme is synthesized by combining the pre-stripper with either the extractive distillation column or entrainer recovery column. Finally, an extractive dividing wall column (EDWC) scheme is synthesized. A fair comparison of all configurations is given under a simulation-based framework employing a stochastic algorithm to optimize all decision variables including the usually arbitrarily fixed operating pressure. The results demonstrate two-column schemes to be more promising, saving more than 30% of economic and environmental costs, and improving energy efficiency by 1–2 times compared to the conventional system. Besides, EDWC structures are not always advantageous in sustainability.